Organic silicon gel for packaging high-power IGBT (Insulated Gate Bipolar Translator) for preventing erosion of hydrogen sulfide gas as well as preparation method and application of organic silicon gel

By preparing a two-component silicone gel with specific components and proportions, the problem of shortened lifespan of IGBT modules in high-temperature and H2S environments was solved, achieving effective H2S blocking and heat resistance, and ensuring the normal operation of IGBT modules in harsh environments.

CN119264870APending Publication Date: 2025-01-07CHENGDU TALY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411393914.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing silicone gels cannot effectively prevent H2S gas corrosion, resulting in a shortened lifespan of IGBT modules in high-temperature and high-concentration H2S environments, and failing to meet the temperature resistance and protection requirements of high-power IGBT modules.

Method used

A two-component silicone gel containing a specific ratio of polysiloxane, polyhydrosiloxane, functional fillers, antioxidants, and catalysts is prepared by vacuum kneading and stirring to form an encapsulation material with excellent heat resistance and barrier properties.

Benefits of technology

It effectively isolates H2S gas corrosion, improves the stability of IGBT modules, meets the flexibility and shock absorption requirements of packaging, ensures long-term stable operation at 220℃, and extends the life of IGBT modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005073188080000041
    Figure BDA0005073188080000041
  • Figure BDA0005073188080000051
    Figure BDA0005073188080000051
  • Figure BDA0005073188080000061
    Figure BDA0005073188080000061
Patent Text Reader

Abstract

The invention discloses organic silicon gel for packaging a high-power IGBT (Insulated Gate Bipolar Translator) for preventing erosion of hydrogen sulfide gas as well as a preparation method and application of the organic silicon gel, and relates to the field of organic silicon gel. The component M comprises polysiloxane with silicon-vinyl structures at two ends, polysiloxane with a silicon-vinyl structure at a single end, polyhydrosiloxane with silicon-hydrogen structures at two ends, polyhydrosiloxane with a silicon-hydrogen structure on a side chain, a functional filler, an antioxidant and an inhibitor; the component N comprises polysiloxane with silicon vinyl structures at two ends, polysiloxane with a silicon vinyl structure at a single end, a functional filler, an antioxidant and a catalyst. According to the material, silicon-vinyl-containing polydimethylsiloxane with different structures and polydimethylhydrosiloxane with different structures are compounded with a functional filler and the like, so that the protection problem of a high-power IGBT (Insulated Gate Bipolar Translator) module in environments with H2S gas, high humidity and the like can be met, and the long-term safe operation of the module is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of organic silicon gel, and in particular to a two-component organic silicon gel material for high-power IGBT packaging for preventing hydrogen sulfide (H2S) gas corrosion, and a preparation method and application thereof. Background Art

[0002] IGBT devices (insulated gate bipolar transistors) are composite fully controlled, voltage-driven, power semiconductor devices composed of BJTs (bipolar junction transistors) and MOSFETs (metal oxide insulated gate field effect transistors). As the "CPU" of power electronic devices, IGBT devices are core devices for energy conversion and transmission. They are widely used in industrial control, new energy vehicles, new energy power generation, variable frequency white appliances, rail transit, smart grids and other fields to form IGBT modules, becoming the most promising power modular products. IGBT modules are usually modular devices that integrate multiple IGBT devices, such as single tubes, diodes, capacitors and other components. The internal components of IGBT modules need to be protected from moisture, dust and vibration, so IGBT modules need to be encapsulated. Silicone gel not only has excellent weather resistance, unique high and low temperature resistance, good hydrophobicity and electrical insulation, but also has the advantages of low internal stress, good impact resistance and strong adhesion. It is currently the preferred material for IGBT module encapsulation.

[0003] In recent years, with the development of power equipment towards high power, high-power IGBT modules have been promoted and applied. High-power IGBT modules need to be used for a long time under conditions of >200°C. Therefore, this field has put forward higher requirements on the temperature resistance of silicone gel encapsulating high-power IGBT modules.

[0004] In addition, when IGBT modules are used in harsh industrial environments such as mining, papermaking, rubber vulcanization, petrochemical processing, and wastewater, they not only face the challenges of high and low temperature shock, water vapor erosion, etc., but also face the risk of high-concentration H2S gas erosion. H2S gas is the most threatening corrosive pollutant to IGBT modules, and can penetrate conventional silicone gel into the interior of the IGBT module. When the IGBT module is operated at high temperature and a certain voltage, the ceramic insulating copper clad board (DCB) in the IGBT module will react with H2S to generate copper sulfide (Cu2S) crystals. This conductive structure gradually spreads inward, causing damage to the internal components and circuits of the IGBT module, and eventually causing a short circuit, resulting in the failure of the IGBT module, greatly shortening the life of the power semiconductor device. Therefore, how to ensure the service life of the IGBT module in the above-mentioned harsh industrial environment is a major challenge in this field. Summary of the invention

[0005] The present invention aims at the requirements of high temperature resistance and H2S gas corrosion resistance of IGBT modules, provides a high temperature resistant and H2S gas corrosion resistant IGBT encapsulation organic silicone gel, and provides a preparation method thereof. The material is prepared by compounding polydimethylsiloxane containing silicon vinyl with different structures, polydimethylhydrogensiloxane with different structures and functional fillers to form a two-component IGBT encapsulation organic silicone gel, which can meet the protection problem of high-power IGBT modules in certain extreme environments and climates (such as the presence of H2S gas, high humidity, etc.) and ensure the long-term safe operation of the module.

[0006] To achieve the purpose of the present invention, the present invention provides an organic silicone gel for packaging a high-power IGBT module for preventing H2S gas corrosion, and its components mainly include:

[0007] (A) polysiloxane having a silicon vinyl structure at both ends (base oil);

[0008] (B) polysiloxane having a silicon vinyl structure at one end (reactive plasticizer);

[0009] (C) Polyhydrogensiloxane (chain extender) with silicon-hydrogen structures at both ends;

[0010] (D) polyhydrogensiloxane (cross-linking agent) containing silicon-hydrogen structure in the side chain;

[0011] (E) functional fillers;

[0012] (F) antioxidant;

[0013] (G) a catalyst;

[0014] (H) Inhibitor.

[0015] The organic silicone gel for packaging high-power IGBT modules for preventing H2S gas corrosion is a two-component organic silicone gel, including an M component and an N component:

[0016] The mass percentages of the components in the M component (100%) are as follows:

[0017] (A) 10-40%

[0018] (B) 10-30%

[0019] (C) 5-40%

[0020] (D) 0.3~20%

[0021] (E) 20~60%

[0022] (F) 0.1~2%

[0023] (H) 0.05~0.2%;

[0024] The mass percentages of the components in the N component (100%) are as follows:

[0025] (A) 20~60%

[0026] (B) 10-30%

[0027] (E) 20~60%

[0028] (F) 0.1~2%

[0029] (G)0.2~4%.

[0030] Optionally, the organic silicone gel for packaging high-power IGBT modules for preventing H2S gas corrosion provided by the present invention is a two-component organic silicone gel, including an M component and an N component. The components of the M component include:

[0031] (A) 10-30% of polysiloxane having a silicon vinyl structure at both ends;

[0032] (B) 15-20% of polysiloxane having a silicon vinyl structure at one end;

[0033] (C) 15-30% of polyhydrogensiloxane having silicon-hydrogen structures at both ends;

[0034] (D) 0.3-2% polyhydrogensiloxane containing silicon-hydrogen structure in the side chain;

[0035] (E) functional filler 30-50%;

[0036] (F) 0.1-2% antioxidant;

[0037] (H) inhibitor 0.05-0.2%;

[0038] Based on 100% mass percentage of N component, the components of N component include:

[0039] (A) 30-50% of polysiloxane having a silicon vinyl structure at both ends;

[0040] (B) 15-20% of polysiloxane having a silicon vinyl structure at one end;

[0041] (E) functional filler 30-50%;

[0042] (F) 0.1-2% antioxidant;

[0043] (G) Catalyst 0.2-4%.

[0044] The following is an introduction to the various components used in silicone gel for high-power IGBT module packaging to prevent H2S gas corrosion:

[0045] Ingredient(A)

[0046] Component (A) is a polysiloxane having a silyl vinyl structure at both ends, and as a base oil, its structure is as follows:

[0047]

[0048] Wherein, R1 can be one or more of methyl, ethyl, phenyl, and vinyl, and each R1 can be the same or different. When all R1 are methyl, component (A) is a polydimethylsiloxane with a silicon vinyl structure at both ends. The larger the value of a, the larger the molecular weight of (A). Wherein a is an integer of 50 to 200, so that the viscosity of (A) at 25°C satisfies 50 to 5000 mPa.s. If the viscosity of (A) is too low, there are too many volatile substances, and volatilization and shrinkage are likely to occur, affecting the heat resistance of the product. If the viscosity of (A) is too high, the product is thick, and defects may occur that affect the packaging effect. At the same time, component (A) is used as a base oil, and its viscosity will also significantly affect the mixed viscosity of the M and N components of the silicone gel. a preferably satisfies the vinyl content of component (A) to be 0.1 to 2wt%.

[0049] The preparation method of polydimethylsiloxane having a silicon vinyl structure at both ends is a conventional method in the art. It is obtained by a balanced reaction of a dimethylsiloxane mixed ring body and 1,3-divinyl-1,1,3,3-tetramethyldisiloxane under the action of an alkaline catalyst. The commercial polydimethylsiloxane base oil having a silicon vinyl structure at both ends can be Andisil VS 50, Andisil VS100, Andisil VS 250, Andisil VS 500, Andisil VS1000, Andisil VS 5000, etc. produced by Anbiya Special Silicone (Nantong) Co., Ltd.

[0050] Ingredient (B)

[0051] Component (B) is a polysiloxane with a silicon vinyl structure at one end, referred to as single-end vinyl silicone oil, which is a reactive plasticizer and has the following structure:

[0052]

[0053] Wherein R2 is one or more of methyl, ethyl, and phenyl, each R2 can be the same or different, when all R2 are methyl, component (B) is a polydimethylsiloxane having a silicon vinyl structure at one end. Component (B) has a viscosity of 100 to 1000 mPa.s at 25°C, and a vinyl content of 0.05 to 0.24 wt%.

[0054] In order to ensure the softness and shock absorption function of the silicone gel material and meet the IGBT packaging requirements, the ratio of vinyl to silicon hydrogen groups in the silicone gel system is greater than 1, and the residual vinyl can undergo an oxidative cross-linking reaction with oxygen under high temperature conditions, resulting in high-temperature aging and hardening of the silicone gel. Component (B) can adjust the cross-linking degree of the silicone gel system, while ensuring the softness and shock absorption function of the silicone gel, reducing the residual vinyl content in the system and improving the heat resistance of the silicone gel material. Single-end vinyl silicone oil is a reactive plasticizer. Its monofunctional reactive group does not increase the cross-linking degree of the system, but plays a role in plasticizing and reducing hardness. At the same time, the single-end vinyl silicone oil will not precipitate after the reaction.

[0055] The polydimethylsiloxane with a silicon vinyl structure at one end can be prepared by referring to the method described in the invention patent CN 111234230B. It is obtained by using a dimethylsiloxane ring body, dimethyl silicone oil, 1,3-divinyltetramethyldisiloxane, etc. in a balanced reaction in proportion under the action of tetramethylammonium hydroxide catalyst and nano-modifier. Commercial polydimethylsiloxane with a silicon vinyl structure at one end can be V15E, V300E, V500E, etc. produced by Wuhan Narabai Pharmaceutical Chemical Co., Ltd.

[0056] Ingredient (C)

[0057] Component (C) is a polyhydrogensiloxane having a silicon-hydrogen structure at both ends, which acts as a chain extender and has a viscosity of 10 to 100 mm at 25°C. 2 / s, with a hydrogen content between 0.02 and 0.15 wt%, commonly known as terminal hydrogen-containing silicone oil. Its structure is shown below:

[0058]

[0059] Wherein R3 is one or more of methyl, ethyl, and phenyl, each R3 may be the same or different, when all R3 are methyl, component (C) is a polydimethylhydrogensiloxane having a silicon-hydrogen structure at both ends. The preparation method of polydimethylhydrogensiloxane having a silicon-hydrogen structure at both ends is well known in the industry, and is obtained by a balanced reaction of tetramethyldihydrogendisiloxane and a dimethylsiloxane ring body under the action of an acidic catalyst such as a cationic resin. Commercial polydimethylhydrogensiloxane having a silicon-hydrogen structure at both ends can be D-15, D-30, D-50, D-100, etc. of Jiangsu Kexing New Materials Co., Ltd.

[0060] Ingredient (D)

[0061] Component (D) is a polyhydrogen siloxane containing a silicon-hydrogen structure in the side chain. As a crosslinking agent, it is a hydrogen-containing polysiloxane with uniformly distributed side hydrogen. Its structure is shown below:

[0062]

[0063] Wherein R4 is one or more of hydrogen, methyl, ethyl, and phenyl, and each R4 may be the same or different. When all R4 are methyl, component (D) is a polydimethylhydrogensiloxane containing a silicon-hydrogen structure in the side chain. d+e is a positive integer of 30 to 60, and the viscosity of component (D) at 25°C is 20 to 100 mm 2 / s, e is a positive integer of 2 to 50, preferably having a hydrogen content of 0.2 to 1.6 wt%. The synthesis method of polydimethyl hydrogen siloxane containing a silicon-hydrogen structure in a side chain is as follows: a high hydrogen-containing silicone oil and a dimethyl siloxane ring body are subjected to a balanced reaction under the action of an acidic catalyst such as a cationic resin. Commercial polydimethyl hydrogen siloxane containing a silicon-hydrogen structure in a side chain can be SH-18, SH-25, SH-36, SH-50, SH-75, etc. produced by Jiangsu Kexing New Materials Co., Ltd.

[0064] Ingredients (E)

[0065] Component (E) is a functional filler, which is selected from alkaline metal / non-metal oxides, metal powders, etc. More specifically, the functional filler can be selected from one or more of fumed silica, aluminum oxide, magnesium oxide, manganese oxide, copper oxide, calcium oxide, ferric oxide, iron powder, and copper powder. The density of the functional filler is 0.5 to 9 g / cm 3 When the functional filler is fumed silica, its specific surface area is preferably 100 to 400 m 2 / g, when the functional filler is the other optional functional fillers mentioned above, it is preferred that the median particle size is 1 to 20 μm. If the particle size of the functional filler is too small, the viscosity of the glue may be too large, and the silicone gel glue may not be fully filled in the small gaps inside the IGBT module, which is not conducive to the application of packaging technology; if the particle size of the functional filler is too large, there is a risk of sedimentation, which affects the insulation and barrier properties of the silicone gel. The functional filler can be a compound of two or more filler particles with different particle sizes. The morphology of any functional filler can be spherical, flaky, needle-shaped, or other amorphous states. However, from the perspective of increasing the filling amount, spherical powders are preferred as functional fillers. The addition of functional fillers gives the silicone gel the ability to block H2S gas.

[0066] Ingredients(F)

[0067] Component (F) is an antioxidant, which may be a hindered phenol compound or a diester compound; the hindered phenol compound is selected from any one or more of 2,6-di-tert-butyl-p-cresol, bis(3,5-tert-butyl-4-hydroxyphenyl) sulfide, and pentaerythritol tetrakis(β-(3,5-tert-butyl-4-hydroxyphenyl) propionate); the diester compound is selected from any one or more of thiodipropionic acid diester, didodecanol ester, and didecanol ester.

[0068] Component (F) is mainly used to delay or inhibit the oxidation process of silicone gel, so that the silicone gel has excellent thermal stability, thereby preventing the silicone gel from aging in a high temperature environment, allowing the silicone gel to work stably for a long time at 220°C, thereby extending the service life of the silicone gel.

[0069] Ingredients (G)

[0070] Component (G) is any one or more of a complex of chloroplatinic acid and a monohydric alcohol, an olefin or an alkyne, a complex of platinum-vinyl polysiloxane or platinum acetoacetate, used as a catalyst to catalyze the hydrosilylation reaction. Commercial catalysts can be selected from Pt-5000 of Shanghai Heraeus Industrial Technology Materials Co., Ltd. or Pt-5000 of Guiyan Platinum Co., Ltd., and the Pt content in these two catalysts is 5000ppm.

[0071] Ingredients (H)

[0072] Component (H) is an inhibitor, which is used to control the silicon-hydrogen reaction rate when the M component and the N component are mixed. Typical inhibitors include acetylene alcohol inhibitors, polyvinyl inhibitors and azo compounds; acetylene alcohol inhibitors include methyl butynol, methyl pentynol, ethynyl cyclohexanol, phenyl butynol, etc., polyvinyl inhibitors include methyl vinyl cyclotetrasiloxane, tetramethyl tetravinyl cyclotetrasiloxane, etc., azo compounds include N, N-diallyl formamide, N, N-diallyl benzamide, etc., and component (H) can select any one or more of them. Component (H) is preferably any one or more of the polyvinyl inhibitors.

[0073] The present invention also provides a method for preparing the organic silicon gel for high-power IGBT packaging for preventing hydrogen sulfide gas corrosion, comprising the following steps:

[0074] (1) Preparation of component M

[0075] According to the proportion of component M, components (A), (B), (E) and (F) are added into a kneader, heated to 40-80° C., and vacuum kneaded for 1-4 hours at a vacuum degree of ≤-0.08 MPa to mix the powder and oil; further heated to 100-140° C., and vacuum dried for 2-6 hours at a vacuum degree of ≤-0.08 MPa to obtain a basic rubber material of component M;

[0076] Add the base rubber of component M into a planetary stirring kettle, add components (H), (C) and (D) in sequence, stir and disperse at a stirring speed of 20 to 40 Hz for 1 to 3 hours, adjust the stirring speed to 5 to 10 Hz, and vacuum degas for 0.5 to 2 hours at a vacuum degree of ≤-0.08 MPa to obtain component M;

[0077] (2) Preparation of N component

[0078] According to the proportion of N component, components (A), (B), (E) and (F) are added into a kneader, heated to 40-80° C., and vacuum kneaded for 1-4 hours at a vacuum degree of ≤-0.08 MPa to mix the powder and oil; heated to 100-140° C., and vacuum dried for 2-6 hours at a vacuum degree of ≤-0.08 MPa to obtain a base rubber material of component N;

[0079] Add the N component base rubber into a planetary stirring kettle, add component (G), stir and disperse at a stirring speed of 20 to 40 Hz for 1 to 3 hours, adjust the stirring speed to 5 to 10 Hz, and vacuum degas for 0.5 to 2 hours at a vacuum degree of ≤-0.08 MPa to obtain the N component.

[0080] The present invention also provides an application of the organic silicon gel for high-power IGBT packaging for preventing hydrogen sulfide gas corrosion, that is, the M component and the N component are evenly mixed in a mass ratio of 1:1 and then used for packaging.

[0081] Compared with the prior art, the present invention has at least the following beneficial effects:

[0082] (1) The organic silicone gel prepared by the present invention can be used for the encapsulation of IGBT modules used in harsh environments, and can effectively isolate the influence of external acidic gases such as H2S on the internal components and circuits of the IGBT module, thereby improving the stability of the module;

[0083] (2) The mixed viscosity of the M and N components of the organic silicone gel prepared by the present invention is 3000-4500 mPa.s, which is moderate in viscosity and can well fill and seal the small gaps of the IGBT module, meeting the existing packaging process;

[0084] (3) The organic silicone gel prepared by the present invention meets the softness and shock absorption function required by the packaging material. At the same time, the residual vinyl content in the organic silicone gel system is small, so that the organic silicone gel has better heat resistance, which is manifested in that the cone penetration change rate of the organic silicone gel elastomer after high-temperature aging, low-temperature aging, high-temperature and high-humidity aging, and high-temperature and low-temperature impact is low, and there are no bubbles and cracks inside the organic silicone gel elastomer; 220°C × 1000h high-temperature aging confirms that the organic silicone gel has excellent thermal stability and can work stably for a long time at 220°C, thereby ensuring the normal operation of the IGBT module in a high-power harsh environment;

[0085] (4) After curing, the silicone gel also has excellent insulation properties, meeting the packaging requirements of IGBTs in power electronic devices. DETAILED DESCRIPTION

[0086] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0087] Preparation methods of silicone gel in various embodiments and comparative examples

[0088] According to the formulas in Table 1 and Table 2, the M component and N component of each embodiment and comparative example were prepared:

[0089] Preparation of component M: Accurately weigh components (A), (B), (E), and (F), add them into a vacuum kneader, and knead them at 60°C in vacuum (vacuum degree -0.09MPa) for 2 hours to mix the powder and oil. Continue heating to 110°C and vacuum (vacuum degree -0.09MPa) drying for 3 hours to obtain the basic rubber material of component M.

[0090] The M component base rubber is added into a planetary stirring kettle, and components (H), (C), and (D) are added in sequence. The stirring speed is controlled at 25 Hz, and the M component is prepared by stirring and dispersing under vacuum (vacuum degree -0.09 MPa) for 30 minutes.

[0091] Preparation of N component: Accurately weigh components (A), (B), (E), and (F), add them into a vacuum kneader, and knead them at 60°C in vacuum (vacuum degree -0.09MPa) for 2 hours to mix the powder and oil. Continue heating to 110°C and vacuum (vacuum degree -0.09MPa) drying for 3 hours to obtain the N component base rubber.

[0092] Add the N component base rubber into a planetary stirring kettle, add component (G), control the stirring speed at 25 Hz, and stir and disperse under vacuum (vacuum degree -0.09 MPa) and remove bubbles for 1 hour to obtain the N component.

[0093] Table 1 Example formulation

[0094]

[0095]

[0096] Table 2 Comparative Example Formula

[0097]

[0098] As shown in Table 2, in comparison with Example 1, Comparative Example 1 cancels component (E), uses component (A), and appropriately increases the amount of component (D) when the amount of component (A) is increased. In comparison with Example 2, component (A) is used to replace component (B), and appropriately increases the amount of component (D) when the amount of component (A) is increased. In comparison with Example 3, component (A) is used to replace component (F).

[0099] When used, the M component and the N component are weighed and mixed in a weight ratio of 1:1, and then cured at room temperature for 24 hours or at 100°C for 1 hour after vacuum degassing. The performance of the silicone gel in each embodiment and comparative example is tested according to the same test standard (such as Table 3), and the results are shown in Table 3.

[0100] Table 3 Basic performance test of silicone gel

[0101]

[0102] From the data in Table 3, it can be seen that the viscosity of Comparative Example 1 is low. Compared with Comparative Example 1, Examples 1 to 3 add fillers to improve product performance and have better electrical properties. The fillers thicken the product, but the product mixing viscosity is moderate, and the construction performance is good, which can fill and seal the small gaps of the IGBT module. The basic performance of the silicone gel of the embodiment and the comparative example during curing is not much different. However, the application environment of the IGBT module will have a significant impact on the performance of the silicone gel. Therefore, it is necessary to test the reliability of the silicone gel material and the reliability of the IGBT module, so as to evaluate the performance of the silicone gel during long-term use.

[0103] In order to evaluate the reliability of the silicone gel material itself, the silicone gel samples of Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to high temperature aging, high and low temperature impact aging, high temperature and high humidity aging, and low temperature aging, respectively, and the changes in appearance and cone penetration of the materials before and after aging under different conditions were checked. The results are shown in Table 4.

[0104] Table 4 Reliability test results of silicone gel materials

[0105]

[0106]

[0107] It can be seen from Table 4 that compared with the comparative example, the appearance of the embodiments after aging under different aging conditions shows that there are no bubbles and cracks inside the silicone gel elastomer, and the cone penetration change rate is smaller, indicating that the silicone gel prepared in each embodiment has better temperature resistance, especially better high temperature resistance, so that the silicone gel can be used for a long time at 220°C.

[0108] In order to evaluate the reliability of silicone gel material encapsulated in IGBT modules, six types of silicone gels according to Examples 1 to 3 and Comparative Examples 1 to 3 were used to encapsulate IGBT modules respectively, and HTRB test, HTGB test, H3TRB test, TST test, TC test, PC test, Vibration test and H2S test were carried out respectively to evaluate whether the silicone gel meets the reliability test requirements of the IGBT module.

[0109] Common IGBT device reliability tests include the following items:

[0110] (1) HTRB (High Temperature Reverse Bias) Test: The HTRB test is used to verify the reliability of the leakage current indicator of the IGBT under stable conditions. The test temperature selected for the HTRB test in this project is 175 degrees, the reverse voltage is 960V, and the test time is 1000h. The focus of the HTRB test is the edge structure and passivation layer of the IGBT chip, as well as ionic contaminants related to production. During the HTRB test, the change of leakage current over time is generally monitored.

[0111] (2) HTGB (High Temperature Gate Reverse Bias) Test: The HTGB test is used to verify the stability of the gate leakage current under electrical and thermal loads; the test temperature selected for the HTGB test in this project is 175°C, the applied voltage is ±20V, and the test time is 1000h. The HTGB test mainly assesses the integrity of the gate oxide layer and mobile ion contamination of the IGBT. It is recommended that the gate leakage current and gate turn-on voltage be continuously monitored during the test. If these two parameters exceed the specified specifications, it is considered that the IGBT module will not pass this test.

[0112] (3) H3TRB (high temperature and high humidity reverse bias) test: The H3TRB test is used to test the effect of humidity on the long-term characteristics of power devices. The test temperature selected for the H3TRB test in this project is 25°C, relative humidity RH85%, reverse voltage 960V, and test time 1000h. The focus of the H3TRB test is the passivation layer of the IGBT and the surface defects of the chip, including the weak links in the entire device structure. If the leakage current is measured immediately after the H3TRB test, it is possible that the leakage current exceeds the standard. The reason is that most IGBT module designs are not completely sealed, and water vapor can also reach the passivation layer over time, resulting in leakage current exceeding the tolerance after the test. Therefore, the device can be baked for 2h to 24h and restored to room temperature for 24h, and then the leakage current of the device can be tested to verify the possibility of water vapor intrusion.

[0113] (4) TST (Temperature Shock Test): The TST test mainly verifies the IGBT's ability to resist mechanical stress under passive temperature changes. The TST test in this project uses a high and low temperature shock of -40 to 150°C, with high and low temperatures staying at the same temperature for 30 minutes, high and low temperature conversion time <1 minute, and 1000 cycles. The focus of the TST test is the packaging of the IGBT module, the connection between the substrate and the ceramic copper clad laminate (DCB).

[0114] (5) TC (temperature cycle) test: The TC test is used to simulate the impact of external temperature changes on IGBTs and verify the overall structure and materials of the device or IGBT module. The TC test of this project uses a high and low temperature cycle of -40 to 150°C, with high and low temperatures staying at 30 minutes each, a heating and cooling rate of 11°C / min, and 1,000 cycles. In particular, the IGBT module is composed of a system of different materials. When heated and cooled, the thermal expansion coefficients of different materials differ greatly, and the mechanical stress on the two interfaces during heating or cooling is greater. The focus of the TC test is the connection between the IGBT chip and the DCB, and the DCB and the substrate.

[0115] (6) PC (power cycle) test: There are two types of power cycles: PCsec and PCmin. During the test, the chip is actively heated to the target temperature through the chip's own working current, and then the current is turned off and cooled to the specified temperature. The PCsec test time for this project is 3 to 5 seconds, the maximum temperature is 150°C, and the cycle is 50 times; the PCmin test time for this project is 3 to 5 minutes, and the maximum power is cycled 50 times. The PCsec test mainly tests the reliability of the near-chip connection; the PCmin test mainly tests the reliability of the near-chip and far-chip connections.

[0116] (7) Vibration test: The vibration test is used to verify the firmness of the mechanical structure and the stability of the electrical connection. It is tested in accordance with GB / T28046.3-2011 Environmental conditions and tests for road vehicle electrical and electronic equipment Part 3 Mechanical loads. It simulates the vibration load of the device during application and verifies the vibration resistance of the device when failure modes (such as structural shedding and material fatigue) occur.

[0117] (8) H2S test: Control the hydrogen sulfide in the aging box: 10×10 -6 ~15×10 -6 (Volume fraction), temperature: (25±2)℃, relative humidity: 75%, put the IGBT module into the aging box and run it for 2000h, evaluate whether the performance of the IGBT module meets the requirements, and disassemble and analyze whether the bonding wires of the IGBT module are corroded.

[0118] Table 5 IGBT module reliability test results

[0119]

[0120] It can be seen from Examples 1 to 3 that the organic silicone gel material prepared by the present invention has moderate viscosity (Table 3), excellent insulation, and excellent reliability under high and low temperature conditions (Table 4). In addition, the product has the ability to block H2S gas, and the IGBT module encapsulated with this material can operate normally in a high-power harsh environment (Table 5).

[0121] Comparative Example 1 does not contain the functional filler, namely component (E), and the H2S gas penetrates the silicone gel and enters the interior of the IGBT module, causing the module to fail (Table 5).

[0122] Comparative Example 2 does not contain single-ended vinyl silicone oil, namely component (B). After high-temperature aging, the cone penetration changes greatly and cracks appear inside (Table 4), and fails to pass the HTRB, HTGB, TST, TC, and H2S tests in the module reliability test (Table 5).

[0123] Comparative Example 3 does not contain an antioxidant, namely component (F). After high-temperature aging, the cone penetration changes greatly and cracks appear inside (Table 4), and fails to pass the HTRB, HTGB, TST, TC, and H2S tests in the module reliability test (Table 5).

[0124] Although the present invention is described herein with reference to the illustrative embodiments of the present invention, it should be understood that those skilled in the art can design many other modifications and implementations, which will fall within the scope and spirit of the principles disclosed in the present application. More specifically, within the scope disclosed in the present application, multiple variations and improvements can be made to the components and / or layout of the subject combination layout. In addition to the variations and improvements made to the components and / or layout, other uses will also be apparent to those skilled in the art.

Claims

1. The organic silicone gel for packaging high-power IGBT modules to prevent H2S gas corrosion is a two-component organic silicone gel, characterized in that: It includes an M component and an N component. The components of the M component include: (A) 10-40% polysiloxane having a silicon vinyl structure at both ends; (B) 10 to 30% of polysiloxane having a silicon vinyl structure at one end; (C) 5 to 40% polyhydrogensiloxane having silicon-hydrogen structures at both ends; (D) 0.3-20% of polyhydrogensiloxane containing silicon-hydrogen structure in the side chain; (E) functional filler 20-60%; (F) 0.1-2% antioxidant; (H) inhibitor 0.05-0.2%; Based on 100% mass percentage of N component, the components of N component include: (A) 20-60% polysiloxane having a silicon vinyl structure at both ends; (B) 10 to 30% of polysiloxane having a silicon vinyl structure at one end; (E) functional filler 20-60%; (F) 0.1-2% antioxidant; (G) Catalyst 0.2-4%.

2. The organic silicone gel for packaging high-power IGBT modules for preventing H2S gas corrosion according to claim 1, characterized in that: Based on 100% mass percentage of the M component, the components of the M component include: (A) 10-30% of polysiloxane having a silicon vinyl structure at both ends; (B) 15-20% of polysiloxane having a silicon vinyl structure at one end; (C) 15-30% of polyhydrogensiloxane having silicon-hydrogen structures at both ends; (D) 0.3-2% polyhydrogensiloxane containing silicon-hydrogen structure in the side chain; (E) functional filler 30-50%; (F) 0.1-2% antioxidant; (H) inhibitor 0.05-0.2%; Based on 100% mass percentage of N component, the components of N component include: (A) 30-50% of polysiloxane having a silicon vinyl structure at both ends; (B) 15-20% of polysiloxane having a silicon vinyl structure at one end; (E) 30-50% functional filler; (F) 0.1-2% antioxidant; (G) Catalyst 0.2-4%.

3. The organic silicone gel for packaging high-power IGBT modules for preventing H2S gas corrosion according to claim 1 or 2, characterized in that: Component (A) is a polysiloxane having a silyl vinyl structure at both ends, and the vinyl content is 0.1 to 2 wt%.

4. The organic silicone gel for packaging high-power IGBT modules for preventing H2S gas corrosion according to claim 3, characterized in that: Component (B) is a polysiloxane having a silicon vinyl structure at one end, and the vinyl content is 0.05 to 0.24 wt %.

5. The organic silicone gel for packaging high-power IGBT modules for preventing H2S gas corrosion according to claim 4, characterized in that: Component (C) is polyhydrogensiloxane having silicon-hydrogen structures at both ends, and the hydrogen content is between 0.02 and 0.15 wt%.

6. The organic silicone gel for packaging high-power IGBT modules for preventing H2S gas corrosion according to claim 5, characterized in that: Component (D) is a polyhydrogensiloxane containing a silicon-hydrogen structure in the side chain, and the hydrogen content is 0.2 to 1.6 wt %.

7. The organic silicone gel for packaging high-power IGBT modules for preventing H2S gas corrosion according to claim 6, characterized in that: Component (E) is selected from one or more of fumed silica, aluminum oxide, magnesium oxide, manganese oxide, copper oxide, calcium oxide, ferric oxide, iron powder, and copper powder.

8. The organic silicone gel for packaging high-power IGBT modules for preventing H2S gas corrosion according to claim 7, characterized in that: Component (F) is selected from any one or more of 2,6-di-tert-butyl-p-cresol, bis(3,5-tert-butyl-4-hydroxyphenyl) sulfide, pentaerythritol tetrakis(β-(3,5-tert-butyl-4-hydroxyphenyl) propionate), diester of thiodipropionate, didodecanol ester, and didecanol ester; component (G) is any one or more of a complex of chloroplatinic acid with a monohydric alcohol, an olefin or an alkyne, a complex of platinum-vinyl polysiloxane, or platinum acetoacetate, and the Pt content in the catalyst is 5000 ppm; component (H) is selected from any one or more of methylbutynol, methylpentynol, ethynylcyclohexanol, phenylbutynol, methylvinylcyclotetrasiloxane, tetramethyltetravinylcyclotetrasiloxane, N,N-diallylformamide, and N,N-diallylbenzamide.

9. The method for preparing the organic silicone gel for high-power IGBT module packaging for preventing H2S gas corrosion according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Preparation of component M According to the proportion of component M, components (A), (B), (E) and (F) are added into a kneader, heated to 40-80° C., and vacuum kneaded for 1-4 hours at a vacuum degree of ≤-0.08 MPa to mix the powder and oil; further heated to 100-140° C., and vacuum dried for 2-6 hours at a vacuum degree of ≤-0.08 MPa to obtain a basic rubber material of component M; Add the base rubber of component M into a planetary stirring kettle, add components (H), (C) and (D) in sequence, stir and disperse at a stirring speed of 20 to 40 Hz for 1 to 3 hours, adjust the stirring speed to 5 to 10 Hz, and vacuum degas for 0.5 to 2 hours at a vacuum degree of ≤-0.08 MPa to obtain component M; (2) Preparation of N component According to the proportion of N component, components (A), (B), (E) and (F) are added into a kneader, heated to 40-80°C, and vacuum kneaded for 1-4 hours at a vacuum degree of ≤-0.08MPa to mix powder and oil; continued to heat to 100-140°C, vacuum dried for 2-6 hours at a vacuum degree of ≤-0.08MPa, cooled the rubber material, and then ground and dispersed it to obtain the N component base rubber material; Add the N component base rubber into a planetary stirring kettle, add component (G), stir and disperse at a stirring speed of 20 to 40 Hz for 1 to 3 hours, adjust the stirring speed to 5 to 10 Hz, and vacuum degas for 0.5 to 2 hours at a vacuum degree of ≤-0.08 MPa to obtain the N component.

10. The use of the silicone gel for high-power IGBT module packaging for preventing H2S gas corrosion according to any one of claims 1 to 8, characterized in that: The M component and the N component are mixed evenly in a mass ratio of 1:1 and then used for packaging.